Realizing the Islamic Banking Consumer Behaviour in Indonesia - Dudi Permana (AMAR (Andalas Management Review), 2022)
The purpose of this study is to analyze the relationship between brand image, product knowledge and perception of profit sharing toward intention to use of Islamic Banking products in Indonesia. Data were obtained by distributing questionnaires to consumers who have not use Islamic Banking products in Indonesia. The collected data was analyzed by using SmartPLS. This study founds that brand image has a positive effect on intention to use, product knowledge has a positive effect on intention to use, and perception of profit sharing has positive effect on intention to use Islamic Baking products. Thus, this study focuses only on the Islamic Banks perspective. For the future researches are recommended to examine the internatl factors of consumers that influence intention to use Islamic Banking such as religiosity, attitude as mediating variable and product knowledge.